Aplikasi Perangkat Bergerak Document Distributions System (DDS): Pengembangan dan Pengujian - Umi Proboyekti; Magdalena Evelyn Halim; Argo Wibowo (Fakultas Teknologi Informasi, 2023)
The company's delivery service must maintain a record of the documents/packages sent to customers or branches. The printed travel document as proof of receipt carried by the messengers must be presented to the shipping operational administrator in order to validate the delivery status of the parcel. In addition, the delivery operational administrator monitors delivery tracing based on the delivery status. The involvement of humans in shipping and administrative procedures causes delays. By developing the DDS application, researchers improve the efficiency of shipping information administration and monitoring. This mobile application's development is supported by the Flutter Framework with a UCD methodology that enables researchers to implement stakeholder requirements. Utilizing interview techniques, formative and summative usability testing, user participation is used to evaluate the efficacy, efficiency, and satisfaction of application users. Application development generates a DDS application that enables electronic monitoring of document/package delivery. The courier updates the delivery status via an application that can be directly monitored by the operational administrator. The test results indicate that the DDS application is one hundred percent effective and efficient, with a satisfaction rating of 4.6% among delivery operational administrators and messengers.